The Business Cycle and Bank Failures - KAYA, Halil Dincer (Journal of Advanced Studies in Finance; Vol 9 No 1 (2018): JASF Volume IX Issue 1(17) Summer 2018DO - 10.14505//jasf.v9.1(17).01, 2018)
In this study, we examine the relation between the business cycle and bank failures in the US. We first look at the frequency of bank failures across expansionary and recessionary periods. Then, we examine the treatment of the failed banks by the FDIC across expansionary and recessionary periods. Finally, we compare the failed banks’ characteristics like total deposits, total assets, and estimated losses across expansionary and recessionary periods. Our results show that the 2001 recession was not a significant period in terms of bank failures. In fact, in terms of failures, the 2001 recession was not worse than the expansionary periods that come before and after it. However, our findings indicate that the 2008 recession has been much more severe compared to the 2001 recession and the expansionary periods. Also, the failed banks during the 2008 recession have been much larger firms with significantly higher loss figures when compared to the banks that failed during the 2001 recession and the expansionary periods. Our results also show that the banks that failed during the 2001 recession had similar characteristics to the banks that failed during the expansionary periods.